2014
DOI: 10.3390/su6117906
|View full text |Cite
|
Sign up to set email alerts
|

Social Evaluation Approaches in Landscape Projects

Abstract: Abstract:Landscape is a crucial component of world heritage and, in the last few years, landscape projects have played a vital role in the development of sustainable scenarios. As reported in the European Landscape Convention, landscape means an area, as perceived by people, of which the character is the result of the action and interaction of natural and/or human factors. Therefore, in landscape planning and assessment, the community is necessarily involved. In order to improve the effectiveness of a project … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 45 publications
0
19
0
1
Order By: Relevance
“…By contrast, UNESCO did not provide models, rules or specific definitions. Its indications, policies and general goals are mainly theoretical and difficult to "translate" into practicable actions and strategies [6,7]. Dongiovanni et al [8] analyzed the MP system of WHS and identified four necessary steps.…”
Section: The Management Plan Of World Heritage Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, UNESCO did not provide models, rules or specific definitions. Its indications, policies and general goals are mainly theoretical and difficult to "translate" into practicable actions and strategies [6,7]. Dongiovanni et al [8] analyzed the MP system of WHS and identified four necessary steps.…”
Section: The Management Plan Of World Heritage Sitesmentioning
confidence: 99%
“…According to Wai-Yin and Shu-Yun (2004) and Miccoli (2014), the concept of sustainability is related to economic, social and environmental values [7,17]. The strategies, actions and best practices provided by UNESCO sites' MPs are linked to ensure economic and social sustainability.…”
Section: The Best Practices Strategies Actions and Measures Appliedmentioning
confidence: 99%
“…As indicated by Miccoli et al (2014), landscape not only has intrinsic value, but also social, environmental and cultural values [11].…”
Section: Introductionmentioning
confidence: 99%
“…The members of the VG are invited to state a preference related to the social importance they attach to the good based on informed and aware choices, to give their opinions and to discuss and even change them [6].…”
Section: The Deliberative Appraisal Proceduresmentioning
confidence: 99%